Education on early detection of pre-eclampsia in pregnant women at Ngimbang Regional Hospital, Lamongan - Lilik Darwati; Husnul Muthoharoh; Asyaul Wasiah; Nining Istighosah (Community Empowerment, 2024)
Pre-eclampsia and eclampsia are the primary causes of maternal and infant mortality and morbidity. The incidence of preeclampsia is 7-10% of pregnancies and it is the second leading cause of maternal death in Indonesia. Preeclampsia can also lead to fetal abnormalities and intrauterine fetal death. Management of preeclampsia focuses on reducing the risk of elevated blood pressure and its treatment. This includes non-pharmacological approaches (such as lifestyle modifications through health education) and pharmacological treatments (medications). The aim of this activity is to enhance pregnant women's understanding of the risks associated with preeclampsia during pregnancy, improve their ability to detect preeclampsia early, and foster public enthusiasm for prenatal check-ups by healthcare providers. The activity involves counselling sessions on preeclampsia and its associated risks, followed by discussions. This program was attended by 10 pregnant women at Ngimbang, Lamongan Regional Hospital. The results indicate an improvement in mothers' understanding of strategies for preventing hypertension during pregnancy.